PRESKRIPSI PENGELOLAAN HUTAN JATI RAKYAT DI KECAMATAN KAHU KABUPATEN BONE SULAWESI SELATAN - Hasanuddin Molo; Hikmah Hikmah; Sulfiana Sulfiana (Gorontalo Journal of Forestry Research, 2021)
ABSTRACTThe purpose of this study was to determine the prescription of community teak forest management in Kahu District, Bone Regency, South Sulawesi Province. Data was collected includes primary data sourced from direct observations in the field, and respondents who are directly involved in the management of community teak forests. Data was collected through observation, interview and survey techniques and literature study. Analysis data was descriptively and quantitatively for the prescription of community teak forest management in Kahu District, Bone Regency. The results was showed that the prescription of community teak forest management applied by the community was still very simple, among others the cultivation system that was implemented only relied on natural seedlings as seed sources. Maintenance carried out in the form of cleaning weeds, pruning and maintenance of growing stubs. Harvesting is done by selecting and cutting down trees after a request from the buyer. The marketing system of teak wood production is divided into 2 ways, namely sales in the form of trees and sales in the form of bearings. The potential of community forests in Kahu Subdistrict of Bone Regency is quite large with an average total volume of 166.4 m³ / ha and a mean annual increment (MAI) of 17.8 m³ / ha / yearABSTRAK Tujuan Penelitian ini adalah untuk mengetahui preskripsi pengelolaan hutan jati rakyat di Kecamatan Kahu Kabupaten Bone, Provinis Sulawesi Selatan. Data yang dikumpulkan meliputi data primer bersumber dari hasil observasi langsung di lapangan, dan responden yang terlibat langsung dalam pengelolaan hutan jati rakyat. Data dikumpulkan melalui Teknik observasi ,wawancara dan survey serta studi pustaka. Analisis data dilakukan secara deskriptif dan kuantitatif untuk preskripsi pengelolaan hutan jati rakyat di Kecamatan Kahu Kabupaten Bone. Hasil penelitian menunjukkan bahwa preskripsi pengelolaan hutan jati rakyat yang diterapkan masyarakat masih sangat sederhana, antara lain sistem budidaya yang diterapkan hanya mengandalkan bibit anakan alami sebagai sumber bibit. Pemeliharaan yang dilakukan berupa pembersihan gulma, pemangkasan serta pemeliharaan trubusan yang sudah tumbuh. Pemungutan hasil hutan kayu yang dilakukan petani selama ini dengan cara memilih dan menebang pohon Ketika sudah ada kepastian pasar dan harga dari pembeli. Model pemasaran kayu jati yang selama ini dilkukan dengan cara menjual dalam bentuk tegakan berdiri maupun dalam bentuk log atau bantalan. Potensi volume pohon pda hutan rakyat yang ada di Kecamatan Kahu Kabupaten Bone cukup besar dengan volume total rata-rata yaitu 166,4 m³/ha dan riap tahunan/mean annual increment (MAI) 17,8 m³/ha/tahu